Impact of DNA Demethylases on the DNA Methylation and Transcription of Arabidopsis NLR Genes - Kong, Weiwen; Xia, Xue; Wang, Qianqian; Liu, Li-Wei; Zhang, Shengwei; Ding, Li; Liu, Aixin; La, Honggui (Frontiers in Genetics, 2020)
Active DNA demethylation is an important epigenetic process that plays a key role in maintaining normal gene expression. In plants, active DNA demethylation is mediated by DNA demethylases, including ROS1, DME, DML2, and DML3. In this study, the available bisulfite sequencing and mRNA sequencing data from ros1 and rdd mutants were analysed to reveal how the active DNA demethylation process shapes the DNA methylation patterns of Arabidopsis nucleotide-binding leucine-rich repeat (NLR) genes, a class of important plant disease resistance genes. We demonstrate that the CG methylation levels of three NLR genes (AT5G49140, AT5G35450, and AT5G36930) are increased in the ros1 mutants relative to the wild-type plants, while the CG methylation level of AT2G17050 is decreased. We also observed increased CG methylation levels of AT4G11170 and AT5G47260 and decreased CG methylation levels of AT5G38350 in rdd mutants. We further found that the expression of three NLR genes (AT1G12280, AT1G61180, and AT4G19520) was activated in both ros1 and rdd mutants, while the expression of another three NLR genes (AT1G58602, AT1G59620, and AT1G62630) was repressed in these two mutants. qRT-PCR detection showed that the expression levels of AT1G58602.1, AT4G19520.3, AT4G19520.4, and AT4G19520.5 were decreased in the ros1 mutant, AT3G50950.1 and AT3G50950.2 in the rdd mutant were also decreased in expression compared to Col-0, while AT1G57630.1, AT1G58602.2, and AT5G45510.1 were upregulated in the rdd mutant relative to Col-0. These results indicate that some NLR genes are regulated by DNA demethylases. Our study demonstrates that each DNA demethylase (ROS1, DML2, and DML3) exerts a specific effect on the DNA methylation of the NLR genes, and active DNA demethylation is part of the regulation of DNA methylation and transcriptional activity of some Arabidopsis NLR genes.